Hydrops fetalis and congenital pulmonary capillary haemangiomatosis in a premature infant - a case report and literature review - Iacoi, Anna; Brobeil, Alexander; Götte, Malena; Enzensberger, Christian; Müller, Vera; Gattenlöhner, Stefan; Axt-Fliedner, Roland (Prenatal Cardiology, 2018)
Pulmonary capillary haemangiomatosis (PCH) is a rare disorder of the lung, well described in adult literature. PCH is characterized by capillary proliferation, infiltrating the interstitium and alveolar walls. This leads to development of respiratory distress and to end-stage pulmonary hypertension. Mostly young adults are affected. The affection of newborn is described in less than ten cases in literature in the past forty years. PCH is a mostly deadly ending disease. We present a preterm born infant with antepartal diagnosed hydrops fetalis, who died 30 minutes after birth. Autopsy revealed PCH as lethal reason and not cardial disease as presumed before.